Growing Anti-Corruption Values ​​Through Islamic Religious Education: Menumbuhkan Nilai-Nilai Anti Korupsi Melalui Pendidikan Agama Islam - Moch. Bahak Udin By Arifin; Nurdyansyah Nurdyansyah; Bukhari Perdana Putra (Universitas Muhammadiyah Sidoarjo, 2023)
Inculcating anti-corruption values is one of the most urgent things to do now. Instilling anti-corruption values can be done in children from an early age. These activities can be carried out consistently and sustainably so that anti-corruption values will become a strong foundation for building attitudes and mentality in children's personalities. A child's personality cannot be formed instantly but requires a long and continuous process. Inculcating anti-corruption values can be done through formal and non-formal education, such as family and the environment around the community, so that the role of parents and an educator is needed for children to continue to guide and set an example of an exemplary attitude towards the application of anti-corruption values. Religious education can also be an essential capital in efforts to teach anti-corruption values by increasing children's faith and devotion; it is hoped that a child will know about the causes and effects of committing acts of corruption in terms of religious law.